National Development Planning In The Field Of State Defense Law - Anang Puji Utama (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
National development planning becomes a very important phase in designing the direction of the nation's and country's growth in the coming periods. Development planning in Indonesia is carried out based on the national development planning system, which encompasses all aspects of community, national, and state life. One of them is the planning in the field of national defense, which has the function of maintaining national existence and stability. The planning of national defense law development faces challenges in accordance with the dynamics of threats, obstacles, challenges, and disturbances to national defense. These challenges arise both at the national, regional, and global levels. National development planning in the field of state defense law is the subject of study in this article. The research method used is normative descriptive research by examining various related literatures. The result of this research is that national development planning in the field of national defense needs to be carried out by considering the dynamics of threats and challenges to national defense. The planning of national defense development requires planning related to the legal framework or regulations in the field of national defense to ensure the legality and legitimacy of the development of the national defense system.